(untitled) (Medico Legal Update, 2020)
The development of an effective vaccine against malaria is essential. Domain Duffy-binding-like (DBL)2? in Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) protein is one of the vaccine candidate proteins because of its binding capacity to ICAM-1 receptor. However, the high polymorphism needs epitope identification before formulating a peptide-based vaccine. This study aimed to identify the conserved epitopes in PfEMP1-DBL2? by an immunoinformatic approach. The protein sequences were analyzed to predict the hydrophobicity attributes, T-cell and B-cell epitopes. T-cell epitopes were identified using the NetCTL and Propred server and analyzed for population coverage rate using the IEDB analysis tool. Moreover, the Bepipred 2.0 and Kolaskar Tangaonkar method combined with the K-means clustering were used to predict the B-cell epitopes. This study found that the hydrophobicity value of PfEMP1-DBL2? recombinant protein is 32.62, indicating that this protein is soluble and potentially fit into HLA alleles active site. Two conserved antigenic CTL epitopes with near 90% population coverage rate in the malaria target population were identified. For Th cell epitopes, the NN-align algorithm showed no overlapping strong binding epitope positions for three chosen Indonesian and African alleles. Three B-cell conserved epitopes were identified at the position of 77-89, 236-254 and 360-377 amino acids with one cluster overlapping with ICAM-1 determinant binding area. The predicted conserved epitopes within the protein in this study are valuable in constructing a subunit peptide-based malaria vaccine candidate. A further experimental study is needed to validate this approach as the next step in vaccine development.